PENGARUH PENGGUNAAN MEDIA INTERAKTIF DAN AKTIVITAS BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA KELAS V SDN SUKABUMI 1 DAN 6 GUGUS 02 TAHUN PELAJARAN 2014/2015 DI KOTA PROBOLINGGO - Dwi Rohyati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This research aims to know the influence of instructional media usage and learning activity on social learning achievement of fifth graders at SDN Sukabumi 1 and 6 Probolinggo. Sixty eight (68) students were invoked as respondents in which thirty four (34) students were from SDN Sukabumi 1 Probolinggo and the rest were from SDN Sukabumi 6 Probolinggo. The results showed that there was significant influence of instructional media usage, learning activities, and instructional media usage and learning activities simultaneously on social learning achievement of fifth graders at SDN Sukabumi 1 and 6 Probolinggo.